The Effects of Work Motivation, Workload, Work Stress, Perceived Organizational Support, and Organizational Citizenship Behaviour on the Performance of Healthcare Workers - Joseph John Rivaldo Kia Bolly; Enrico Adhitya Rinaldi; Nurcahyo Andarusito (International Journal of Health and Pharmaceutical (IJHP), 2026)
The success of Dharmawangsa Specialized Hospital in achieving its mission to provide comprehensive mental health services greatly depends on the performance of its healthcare workers. Pre-research data indicate a negative trend in the number of healthcare workers with excellent performance, declining from 17.64% in 2022 to 9.52% in 2024. This study aims to analyses the effects of work motivation (X1), workload (X2), work stress (X3), Perceived Organizational Support (POS) (X4), and Organizational Citizenship Behaviour (OCB) (X5) on the performance of healthcare workers (Y) at Dharmawangsa specialized hospital. This study used a quantitative approach with a cross-sectional design. The accessible population consisted of all healthcare workers actively working at Dharmawangsa, totalling 42 respondents selected through total sampling. The data were analysed using the SEM-PLS method with Smart-PLS v4 software. The results of hypothesis testing showed that work motivation had a negative and insignificant effect on performance (T-statistic = 0.389; p-value = 0.697), workload had a positive and significant effect on healthcare worker performance (T-statistic = 2.189; p-value = 0.029), work stress had a positive and significant effect on healthcare worker performance (T-statistic = 2.116; p-value = 0.034), POS had a negative and insignificant effect on performance (T-statistic = 0.544; p-value = 0.587), and OCB had a positive and significant effect on healthcare worker performance (T-statistic = 2.424; p-value = 0.015). This study concludes that workload, work stress, and OCB are proven to have a significant effect on the performance of healthcare workers at Dharmawangsa Specialized Hospital Indonesia.